The Relationship Of The Anterior Dental Malocclusion With The Incidence Of Gingivitis In Students Of Medical Faculty in Surabaya - Nike Ade Therinda; Wahyuni Dyah Parmasari (Sriwijaya Journal of Dentistry, 2022)
Introduction: Gingivitis is an inflammation of the gums, which is the initial stage of gum and periodontal tissue disease, characterized by red gingival tissue, bleeding easily, bad breath (halitosis), and the presence of debris on the teeth and cervical area. Misaligned tooth is said to be one of the predisposing factors for gingivitis. Purpose: To determine the relationship between the arrangement of the anterior mandibular teeth with the incidence of gingivitis in students of the Faculty of Medicine, Wijaya Kusuma University, Surabaya. Methods: This study used a purposive sampling method with a total population of 125 subjects. From this population, 56 people were taken who experienced anterior crowding with gingivitis. The degree of malocclusion, i.e. anterior crowding, was examined clinically and was associated with gingivitis. The data obtained were analyzed by Chi-square test. Results: There is a significant relationship between the anterior mandibular malocclusion and the incidence of gingivitis (p< 0,05). Conclusion: Anterior tooth arrangement affects the incidence of gingivitis among medical faculty students in Surabaya.